Feasibility of a smartphone app to monitor patient reported outcomes in multiple sclerosis: The haMSter interventional trial - Patrick Altmann; Markus Ponleitner; Tobias Monschein; Nik Krajnc; Gudrun Zulehner; Tobias Zrzavy; Fritz Leutmezer; Paulus Stefan Rommer; Barbara Kornek; Thomas Berger; Gabriel Bsteh (Digital Health, 2022)
Background Monitoring of patient outcomes in multiple sclerosis (MS) is fundamental for individualized treatment decisions. So far, these decisions have been motivated by conventional outcomes, i.e., relapses or clinical disability supported by radiological disease activity. Complementing this concept, patient reported outcomes (PROs) assess individual health-related quality of life, among other constructs. Their inclusion in clinical routine, however, has been challenging as assessing them requires resources of time and personnel. Objective This interventional feasibility study investigated the haMSter app, a mobile health solution for remote and longitudinal monitoring of PROs in a sample of people with MS (pwMS). Methods The core feature of haMSter is the provision of three PRO questionnaires relevant to MS (anxiety/depression, MS-related quality of life, and fatigue) that patients can fill out once a month. For this feasibility trial, we offered 50 volunteers to use the haMSter app over six months and to take part in a haMSter study visit. This consultation concluded the study and participants had the opportunity to discuss their graphically plotted PRO results with their treating physician. Results The main outcome was overall patient adherence to monthly completion of the PRO questionnaires, which remained high up to 4 months (98%) and dropped over time (months 5: 83% and 6: 66%). Exploratory outcomes included patient satisfaction as estimated on the Telemedicine Perception Questionnaire (TMPQ, 17–85 points). The mean TMPQ score was 64 (95%CI: 62–66) points, indicating a high degree of approval. Ancillary tests included subgroup analyses of participants with particularly high or low satisfaction and upper extremity disability as a potential obstacle to utility or acceptance. We found no distinct characteristics separating participants with high or low satisfaction. Conclusions In this first feasibility trial, the haMSter app for longitudinal PRO monitoring was well received in terms of adherence and satisfaction. ClinicalTrials.gov identifier: NCT04555863.